KEPENTINGAN INDONESIA MENGGUGAT UNI EROPA TERKAIT MINYAK SAWIT DAN BIOFUEL DARI TANAMAN KELAPA SAWIT MELALUI WORLD TRADE ORGANIZATION (WTO) PADA KODE KASUS DS593 - Bayti, Tiara Nur; Iskandar, Irwan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2026)
This research analyzes the national interests underpinning Indonesia's decision to file a lawsuit against the European Union (EU) at the World Trade Organization (WTO) through dispute DS593. The lawsuit was a response to the EU's Renewable Energy Directive II (RED II) policy, which classifies palm oil as a high-risk crop (High ILUC-Risk) and mandates a gradual phase-out until 2030. This study employs a qualitative approach with a descriptive-analytical method. Data collection techniques were conducted through literature reviews and document analysis, encompassing the RED II policy and the DS593 dispute filings. The research utilizes the perspective of Institutional Liberalism, the Nation-State Level of Analysis, and Donald E. Nuechterlein’s Concept of National Interest to analyze the dimensions of the interests pursued by Indonesia. The results indicate that the RED II policy is a form of EU "green protectionism" stemming from a lack of competitiveness in land efficiency. Indonesia's lawsuit was driven by economic interests to mitigate foreign exchange losses of USD 1.59 billion per year, protect the welfare of smallholders due to an export decline of up to 66.3 percent, and maintain legitimacy. Furthermore, there is a world order interest to combat discriminatory trade practices. This litigation effort successfully proved that the EU's procedures violated the TBT Agreement and GATT 1994, leading to an agreement by the European Union to revise its regulations in February 2026. Keywords: DS593 Dispute, Palm Oil, Green Protectionism, National Interest, WTO.